ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU BOLU SALAK MENGGUNAKAN METODE ECONOMYC ORDER QUANTITY (EOQ) PADA UD BOLU SALAK KENANGA KOTA PADANG SIDIMPUAN - Surya Dinung Hasibuan; Emmia Tambarta Kembaren; Sakral Hasby Puarada; Eva Wardah; Fadli (Jurnal Mahasiswa Agribisnis, 2025)
This research was conducted in Padang Sidimpuan City. This research was carried out becausePadang Sidimpuan City is one of the snakefruit producing cities which is currently developing as afarming commodity. Salak in Padang Sidimpuan City is utilized and developed by every company toprovide added value or profitable prices, one of which is UD Bolu Salak. However, it is felt thatmanaging the supply of raw materials by the company is not optimal, so researchers use theEconomic Order Quantity (EOQ) method to optimize the supply of raw materials in the company.This research aims to analyze the control of the supply of raw materials for salak sponge cake at UDBolu Salak Kenanga, Padang Sidimpuan City, using the Economic Order Quantity (EOQ) method.The sampling technique was carried out using the purposive sampling method. The research methoduses a quantitative descriptive approach, namely analyzing the control of the supply of raw materialsfor at UD Bolu Salak. The research results show that the company's policy inventory costs are IDR11,400,000.00 for each raw material. This policy is considered not optimal because excess purchasesoften occur which causes wasted costs. On the other hand, using the EOQ method provides moreefficient results. The inventory costs generated by the EOQ method for each raw material are aroundIDR 1,310,000.00 per year, which is much lower than the company's policy. The Safety Stock analysisshows that the need for reserve supplies for wheat flour is 18,400 kg, granulated sugar 3,591.68 kg,snake fruit 3,116.68 kg, and eggs 7,095 squares, which is not accommodated by company policy.Meanwhile, the Reorder Point (ROP) based on the EOQ method occurs at certain minimum inventorylevels, such as 64.64 kg of wheat flour and 32.18 kg of granulated sugar, while company policy doesnot stipulate ROP.Keywords: Inventory Control, Raw Materials, Salak Cake, Economic Order Quantity (EOQ), CostEfficiency